Synergistic Antibacterial Activity of Allium sativum (Garlic) Extracts and Skimmed Milk on Some Bacterial Isolates - Usman, R. A.; Taura, D. W.; Mukhtar, M. D.; Yakasai, A. A. (UMYU Journal of Microbiology Research)
As part of the on – going search for potent and resistant – free antimicrobial medicinal plants, the antibacterial and synergistic effects of Allium sativum and Skimmed milk on some bacterial isolates were investigated. The antibacterial activity of garlic/ milk extracts was assayed by the agar well diffusion method. The methanol garlic extracts inhibited the bacterial isolates whilecoli was resistant. The highest activities were on K. pnuemoniae (14mm) closely followed byS. typhi (13mm) and aureus (13mm) and then S. pnuemoniae (12mm). The synergistic effect of garlic and skimmed in combination gave a stronger activity on K. pnuemoniae being more susceptible with a zone of inhibition of 16mm and E. coli (13mm) which was resistant to individual garlic extract. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of garlic/milk combination on E. coli were 625µg/ml and 1250 µg/ml respectively. This indicated the potency of the combination. The findings of this study also confirm the use of garlic milk decoction in the treatment of ailments caused by these microorganisms. Therefore this synergistic effect can be used to design good therapeutic approach to combat with bacterial pathogens.